Effects of Genetically Modified (GM) Maize Adoption in Small Scale Farms on Cropping Systems of the Eastern Cape Province, South Africa - Kadango, Tendayi Lovemore; Assefa, Yoseph; Mnkeni, Pearson Nyari Stephano (The International Journal of Biotechnology, 2020)
Genetically modified (GM) crops are being promoted to ensure agricultural productivity and food security to keep pace with the ever-growing global population and food demand. In as much as agricultural technological advancements are crucial, there is need to strike a balance with agrobiodiversity for sustainable farming. Surveys were conducted in five municipal districts of the Eastern Cape Province to determine GM-technology adoption effects on maize cropping systems, agronomic practices and farmers’ perceptions of production constraints. Interviews of 232 farmers, independent (IF) 22.4% and government sponsored (GCP) 77.6%, revealed a wide variation in agronomic practices amongst them. Results indicate significant differences on the maize cropping systems practiced by the Eastern Cape small scale farmers. The majority (81.7%) of interviewed small scale GCP farmers produce maize as a monocrop, under dryland (91.7%) through conventional tillage practices (100%). In contrast, IF farmers practiced maize sole cropping (34.6%), under dryland (90.4%) through conventional tillage practices (86.5%). There were significant differences between the two farmers’ groups on crop mixture used (p=0.00), crop rotations (p=0.02), choice of maize varieties (p=0.00) and fertiliser use (p=0.00). Demographic and farm characteristics, type of land cultivation, production constraints, pest problems and pest management practices are discussed. The findings suggest the need to devise a system that will improve compatibility of GM-maize technology and traditional farming practices to ensure sustainable farming and food security for the resource poor farmers. The government support schemes seeking to enhance agricultural productivity need to equip farmers with the necessary versatile farming skills.